(N‐Phosphinoamidinate)cobalt‐Catalyzed Hydroboration: Alkene Isomerization Affords Terminal Selectivity. Issue 43 (3rd September 2014) - Ruddy, Adam J.; Sydora, Orson L.; Small, Brooke L.; Stradiotto, Mark; Turculet, Laura
Abstract: Herein we establish the utility of a three‐coordinate ( N ‐phosphinoamidinate)cobalt(amido) pre‐catalyst that is capable of effecting challenging alkene isomerization/hydroboration processes at room temperature, leading to the selective terminal addition of the boron group. Abstract : Chain‐walking hydroborations : A three‐coordinate ( N ‐phosphinoamidinate)cobalt(amido) pre‐catalyst is capable of effecting challenging alkene isomerization/hydroboration processes at room temperature, leading to the selective terminal addition of the boron group.